The Effectiveness of Game Methods for Increasing Children's Interpersonal Intelligence in Paud Abdi, Tanjung Tiram District Batu Bara Regency - Asmidar Parapat (International Journal of Management, Economic and Accounting, 2023)
This research aims to describe the effectiveness of the game method for developing children's interpersonal intelligence in PAUD Abdi, Tanjung Tiram District, Batu Bara Regency. The object of the research is a game method for developing children's interpersonal intelligence in PAUD Abdi, Tanjung Tiram District, Batu Bara Regency. This research uses a qualitative approach with a case study type of research. Research data was obtained through interviews, observation and documentation. The collected data was analyzed descriptively qualitatively using an interactive analysis model. The validity of the research data was re-tested using extended participation, persistence of observation, and triangulation.